Nurse-led telephone outreach for a COVID-adapted suspected colorectal cancer pathway. (2nd February 2021) - Bell, Sheila E; Crawford, Jill; Gunn, Frances; Noble, Colin; Miller, Janice; Dunlop, Malcolm G; Maeda, Yasuko; Din, Farhat VN
Abstract : Background: COVID-19 has brought about unprecedented challenges to healthcare services in the UK. The pandemic led to the cessation of colonoscopy and outpatient clinics. A bespoke COVID-adapted cancer pathway, using computed tomography (CT) scanning and the quantitative faecal immunochemical test (qFIT), was introduced to mitigate the risks of patients referred with potential colorectal cancer. Aims: This study aims to evaluate the workload of patient telephone calls undertaken by nurses and their impact on the operation of the pathway. Methods: Data were collected prospectively and analysed to assess the volume of patient flow, number of calls made and content of conversations. Findings: During a 2-month period, 975 patients (56.6% female, median age 63 years) were registered on the COVID-adapted cancer pathway. The 45.9% (n=448) of patients who did not return qFIT tests in a timely manner were contacted. Of these, 9.4% (n=42) requested to postpone or declined an appointment. Most were appreciative of the opportunity to clarify the rationale of the pathway and address any concerns. Conclusions: Phone calls made and received by nursing staff were helpful to discuss patient concerns and increase patients' understanding of the alternative treatment options available during the pandemic.